Distribution of Botulinum Toxin-Producing Clostridia in Soils of Argentina - Lúquez, Carolina (2005)
We studied the presence of botulinum toxin-producing clostridia in 2,009 soil samples from five geographical regions of Argentina. The prevalence was 23.5%, and the distribution was not homogeneous among the regions. We observed a great multiplicity of serological types and a higher prevalence in nonvirgin soils than in virgin soils.